Estudo do efeito de Doxorrubicina combinada com DisBa-01 sobre a migração e transição-epitelial-mesenquimal em células tumorais de mama - Machado, Aline Maria (Universidade Federal de São Carlos, 2025)
In breast cancer, αvβ3 integrins are involved in tumor progression and the development of metastases, as well as acting in the acquisition of resistance to antineoplastic therapies. We propose to evaluate the effects of the combined treatment of doxorubicin and DisBa-01, a recombinant disintegrin obtained from Bothrops alternatus, on the migratory and invasive capacity and epithelial-mesenchymal transition of breast tumor cells. We hypothesized that the combined treatment could potentiate the effects of chemotherapy by modulating cell-matrix interactions. The expression and purification of DisBa-01 was carried out, along with the evaluation of the expression of integrins αv and β3 in ER+PR+ and TNBC cell subtypes. The IC50 of doxorubicin was determined, followed by assessment of cell viability by combined treatment. The analysis of collective and individualized cell migration was conducted along with the evaluation of epithelial-mesenchymal transition, considering the activity of matrix metalloproteinases (MMPs) and invasion into fluorescent gelatin matrix. To compare the 2D and 3D culture models, DisBa-01 internalization assays, morphology and cell viability analyses were carried out. The results showed that MCF-7 (ER+PR+) and MDA-MB-231 (TNBC) cells exhibited distinct αv and β3 integrin expression profiles and differentiated responses to doxorubicin. In MCF-7 cells, the combined treatment promoted a reduction in cell invasion, cell viability and circularity in two-dimensional models. In three-dimensional models, the same treatment resulted in more cohesive spheroids for this same lineage. With regard to MDA-MB-231 cells, there was a reduction in invasion, cell viability and circularity in 2D models, as well as a reduction in cell migration, both individually and collectively. In conclusion, it is proposed that the combined treatment of DisBa-01 and doxorubicin has an additive effect, making it possible to reduce the dosage of chemotherapy when combined with disintegrin, which may reduce cytotoxic effects in future studies.
Study of the effect of Doxorubicin combined with DisBa-01 on migration and epithelial-mesenchymal transition in breast tumor cells
Keywords: Câncer de mama; Integrinas; Transição epitelial-mesenquimal; Breast cancer; Integrins; Epithelial-mesenchymal transition; CIENCIAS BIOLOGICAS